O currículo na educação de jovens e adultos: uma experiência em construção - Rita Aparecida Rocha (2008)
This study approaches the educational field for young and adults, with the purpose of elaborating a curriculum for this public. With theorical background in curriculum production, education for young and adults, and social education, the text intends to explain how the schools produces and work their curriculum for this public, and also will try to point out thoughts and contributions for its elaboration. It also shows how this experience can advance and produce time and space, considering the particularities of young and adults students, in a curricular point of view, still marked by a disciplinary culture, and in the young and adults students field, by the systematization of effective purposes to work with this public. The study had as reference, the school that I worked as a coordinator, during the period from 2001 to 2007. The informations occurred during activities that happened inside and outside the classrooms, promoted in other social environments, while capacitating educators, and during other times destined to think and evaluate the curriculum for young and adults students. This study is a result of my course, and as my experience as an educator in the social area, in academic studies, as a coordinator, and with discussions concerning the educational policies.